The European Commission’s proposal for a regulation on Standard-Essential Patents : An in-depth analysis on the aims, measures and potential consequences of the proposed framework - Paappa, Riina (My University, 2023)
This master’s thesis introduces an in-depth analysis to the aims, measures and potential consequences of the recently proposed EU-wide Standard-Essential Patent framework, which was published by the European Commission in April 2023. This paper utilizes legal docmatics as a method in order to provide the most comprehensive insight into the current regulation on Standard-Essential Patents, the proposed initiative and the potential consequences of the initiative. While analyzing the potential consequences of the proposed framework, an economic aspect has also been intertwisted with the aforementioned method of legal docmatics. The key purpose of this thesis is to raise awareness and shed light into the potential impacts of the suggested measures. Furthermore, the objective of this thesis is not only to function as an enlightening resource of information for the stakeholders, but everyone interested in the field. Based on the investigation connected to the writing process of this thesis, this thesis claims that there is not enough legitimate evidence on the necessity of establishing a regulatory intervention in the field of SEPs within the EU. Moreover, this thesis argues that if the proposed initiative will be set into force in its current form, the whole European leadership within the field of technology will potentially be highly jeopardized. Therefore, this thesis strongly suggests that the European Commission should take another look at the proposal and seriously reconsider its’ content and measures.
Keywords: Standard-Essential Patent, SEP, FRAND Commitments, SEP Litigations, Roalty-rates, European Commission, EU